Rainfall dynamics in the Sudano-Sahelian zone of Nigeria under RCP 8.5 - Adegun , Olubunmi; Odunuga, Shakirudeen (Bulletin of Geography. Physical Geography Series, 2022)
The study analysed the historical (1961–90) and projected rainfall variability for the rainy season expected in the near future (2021–50) at selected locations within the Komadugu-Yobe and Sokoto-Rima River Basins in the Sudano-Sahelian zone of northern Nigeria. Three models were utilised, and analyses were based on Representative Concentration Pathway (RCP) 8.5. Projected changes in mean, level of variability and distribution of rainfall were analysed using the Relative Percentage Change Method and the Precipitation Concentration Index (PCI), while the performance of the models was evaluated using the Nash–Sutcliffe Efficiency (NSE) index. The results show that changes in mean rainfall will be predominantly negative, with a minimum and maximum level of change of ˗1.02 per cent at Nguru, and ˗70.4 per cent at Jos, based on the IPSL-CM5A and HadGEM2-ES models, respectively. The rainy season of the baseline period varied between low and moderate variability, while the near future ranges between low and high levels of variability. The validation indicates acceptable levels of performance, with most values ranging between 0.0 and 1.0. The PCI for the near future suggests that the rainy season will be mainly characterised by uniform and near-uniform rainfall distribution. Hence, the projected negative changes and high variability of rainfall at some locations call for the development of an Adaptive Benefit Mechanism that will minimise future natural resource conflicts.